Quality of customer service, lean service and agility tools in the contact center of companies from the telecommunications sector: a review of the literature - Mautino Guadalupe, Angie Sofia (2024)
In recent years, the telecommunications sector has become an important item in the world, with globalization and the increase in technologies, people increasingly seek to be connected to the Internet and obtain network services that meet their requirements. It is for this reason that companies are focusing their objectives on achieving a higher level of user satisfaction and for this they implement various tools. One of the methodologies that has helped certain companies to raise their level of user satisfaction by focusing their processes on the elimination of changes and other activities that do not generate value. That is why this research focuses on implementing the Lean Six Sigma DMAIC methodology and combining it with the Agile methodology, in order to insert a culture of employee participation and commitment from the beginning of the project. When reviewing different articles, it was found that there are few articles that combine these two methods in telephone operators. According to the results obtained by the case studies, a reduction in the waiting time for answering calls, a reduction in the resolution time of customer requests, an increase in the performance index of the customer service process and a reduction in rework that does not add value to the processes.